Lethal Efficacy of Banana Leaves Extract (Musa paradisiaca L.) Against Aedes aegypti Larvae: Daya Bunuh Ekstrak Daun Pisang (Musa paradisiaca L.) Terhadap Larva Aedes aegypti - Karima, Wihdatul; Ardiansyah, Syahrul (Universitas Muhammadiyah Sidoarjo, 2021)
Indonesia has a potential to be exposed to the threat of dengue hemorrhagic fever with the point vector, the Aedes aegypti mosquito, so development need to be stopped. The use of synthetic larvicides in eradicating mosquito larvae can cause environmental pollution. To reduce it, an alternative is needed using plant larvacides with banana leaf. Banana leaves are obtained from Candi Sidoarjo. Ethanol extract of banana leaf contains tannin compounds, alkaloids, terpenoids, saponins, and flavonoids which can be used as larvicides. This research was conducted to determine the toxic effects of banana leaf extract (Musa paradisiaca L.) on the larvae of Aedes aegypti mosquito mortality. This research was conducted using the post test only the control group design with 6 treatment groups including control (aquades) and banana leaf extract concentrations of 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm. This study used third instar larvae, each test group countaining 20 larvae with 4 repetitions. That obtained were analyzed using data and probit tests. The results of this study that banana leaf extract has a toxic effect on Aedes aegypti mosquito larvae with LC50 at a concentration of 4638 ppm.